THE ESTIMATION OF TOURIST AND RECREATIONAL POTENTIAL OF INDIVIDUAL TERRITORIES OF THE REGION CAUCASIAN MINERAL WATERS - Andrey Vadimovich Baturov; Valentina Fedorovna Kshishnevskaya (Современная наука и инновации)
The work considers methods of estimation of touristic and recreation potential of the Caucasian Mineral Waters. Integrated estimation of touristic and recreation potential of region had carried out by rating method.